Relevance of diatom testing on closed organs of a drowned cadaver who died after receiving treatment for 10 days: A case report - Tsuneya, Shigeki; Yoshida, Maiko; Hoshioka, Yumi; Chiba, Fumiko; Inokuchi, Go; Torimitsu, Suguru; Iwase, Hirotaro (Legal Medicine, 2023)
•This is a case of an autopsy performed on a man who died 10 days after drowning.•More than 100 diatoms per gram were detected via a diatom test of the lung samples.•Only two diatoms were detected from approximately 34 g of closed organ samples.•The diatom test of closed organs might no longer be necessary. A male in his late adolescence fell into the sea and was found 50 min later with cardiopulmonary arrest. He was revived approximately 260 min after he drowned. Although he received several treatments, including venoarterial extracorporeal membrane oxygenation and continuous hemodiafiltration, he was clinically diagnosed with brain death. He died 10 days after the accident. The autopsy did not reveal any unremarkable findings other than those associated with post-resuscitation changes and medical treatment. The diatom test revealed 47.9, 311.6, and 577.5 diatom particles per gram from water, left lung, and right lung samples, respectively. No diatoms were detected in a 10 g liver sample, and 1 diatom was detected in each of approximately 12 g of bilateral kidney samples, which was different from the abundant species in the lung samples. The diatom test of the closed organs could be considered false negative for confirming drowning death since diatoms can also be detected in non-drowned cadavers on dry land. This suggests that diatoms might not reach the closed organs via circulation and that the diatom test of closed organ samples might no longer be necessary to confirm drowning deaths.